Developing Statistics Learning Equipment Based on the PMRI Approach Oriented to Students’ Statistical Reasoning Ability - Kesumawati, Nila; Octaria, Dina (Universitas Islam Raden Intan Lampung, INDONESIA, 2019)
This development research aims to produce valid, practical, and effectivelearning equipment. The developed learning equipmentincludesemester learning plans (RPS), student worksheets (LKM), and test questions in basic statistics courses using the PMRI approach oriented to statistical reasoning ability. This study employs the ADDIE development model. The quality of the product was assessed based on the validity, practicality, and effectiveness aspects. The result shows that the validity quality of the learning equipment has fulfilledthe valid criteria indicated by the average score of semester learning plans of 3.75 and the average score of the student worksheet of 3.70. The practicality of learning equipmenthas met the practical criteria indicated by the students’ questionnaire responsesscore of 3.125 and the results of learning implementation observation of 90.17. The effectiveness shows a score of 15% with low effective criteria, although based on the results of students’ answers as a whole,the students' statistical reasoning is at level 3 (Procedural Reasoning).